HUBUNGAN MEDIA SOSIAL DENGAN KETERAMPILAN MENULIS PARAGRAF ARGUMENTASI MAHASISWA DI POLITEKNIK NEGERI BATAM - Lubis, Eka Mutia (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2019)
This study aims to determine the relationship between social media and the argumentative paragraph writing skill of Politeknik Negeri Batam students. This study employs a descriptive method, with 70 students as the research subjects. In this study, students were asked to do a practice in the form of writing an argumentative paragraph. An analysis from the obtained data is then conducted to find out their mastery in composing a paragraph. As the basis for the assessment, scores in unity, coherence, and development aspect were assigned to each paragraph. These three aspects were then collected and summed up to find the mean of the data, which had been grouped and assigned score before, to determine their mastery level in writing an argumentative paragraph. Subsequently, the data were inserted into a table. Based on the table, which recapitulates the mastery level in writing an argumentative paragraph, the results are as follows: 43 % of the students have a high level of mastery, with 58 % of them having access to social media; 37 % of the students are in the medium level of mastery, with 28 % of them having access to social media; 20 % is in the low level of mastery, with 13 % of them having access to social media. The results of this study show that students who are active in social media have the ability to write a good argumentative paragraph. This might be due to the fact that activities in social media enhance their writing skill, which is closely related to the four aspects of language competencies, which consist of observing, reading, listening, and writing.